Investigation of Thermoresponsive Microgel Polymer Swelling Theory. (1st October 2020) - Agbim, Kenechi A.; Schaefer, Laura A.
Abstract: This review details the challenges with the canonical polymer swelling theory in its ability to accurately estimate realistic polymer swelling behavior. It is important to quantify this behavior since the development of new and hybrid materials with dynamic environmental response is expected to drive rapid growth and innovation in markets including biomedicine, electronics, pharmaceuticals, building and infrastructure, and aerospace. As many of these markets require high precision and controlled dynamic response, hydrogels are being investigated to help address some of the heat transfer and fluid flow challenges found in these applications. Stimuli-responsive materials usually respond to one stimulus (e.g., light, temperature, etc.) However, hybrid polymer materials that respond to multiple stimuli can be developed through the mixing of monomer chains with differing behaviors. For these materials, the synthesis conditions influence the polymer behavior in changing environmental conditions, and it is imperative to develop a deeper understanding of how the preparation of the polymer networks impacts the viscoelastic nature of the polymer. The work also discusses the influence that synthesis conditions have on the behavior of thermo-responsive Poly(N-isopropylacrylamide) (PNIPAAm). Lastly, the paper describes an inferential, nested regression model developed to highlight the dependence the swelling has on the synthesis technique used.